Phosphorylation of pregelatinized maranta starch (Maranta arundinaceae L.) as theophyllin tablet matrix controlled release - Effionora Anwar; Dina Yusmarlina; Hasan Rahmat; Kosasih . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
The present study was carried out to investigate the effect concentration level of pregelatinized and pregelatinized marantha starch phosphate as matrix polymer on the drug release profile. Pregelatinization starch was made by heating suspension of marantha starch with drum dryer. Phosphorylation of pregelatinized maranta starch was prepared by reacting pregelatinized marantha starch with Na2HPO4 and NaHPO4 (2:3). The modified starch product was used as matrices for tablet controlled release separately by direction compression process. Theophyllin was used as a model drug hydrophobic. The dissolution test was carried out separately in 0,1 N HCl (pH 1,8) and in phosphate buffer (pH 7,2), both for 8 hours by using paddle method.The result showed that there was no significant difference (P< 0,05) among the drug release profile from different level concentration of polymeric matrices. The drug release rate was found to be governed by the type and concentration level of polymer in matrix system, polymeric concentration (25%) in matrix, the slower release rate of the drug. Release profile showed a tendency to follow zero-order kinetics from all matrix tablets, and the drug release may be controlled by combination of diffusion and erosion delivery system.Key words: pregelatinized maranta starch phosphate, controlled release, polymeric matrices.